P18 Exploring quantitative relationships between serological results and stage of syphilis. (18th May 2015) - Denman, Johanna; Fernando, Imali
Abstract : Background/introduction: There has been little published regarding quantitative results of newer serological assays in infectious syphilis. Previous studies have shown an association between VDRL and TPPA titre and stage of syphilis; with higher titres in secondary syphilis. Aim(s)/objectives: To examine quantitative relationships between serological results and stage of syphilis including newer assays. Methods: Early syphilis cases diagnosed March 2011–August 2014 were identified from a sexual health clinic database. Cases classified as primary, secondary and early latent by clinical diagnosis. Serology results were recorded including TPPA, VDRL (used until 01/03/2012), RPR (used from 01/03/2012), IgG (Abbott Architect Total Antibody Test), and IgM (lab21 IgM EIA). Results: 155 patients included. 149 male, 6 female. Average age 38. 92% men were MSM. 32% HIV positive. 33% classified as primary, 21% secondary, 46% early latent. 64% new diagnoses, 36% re-infected. Discussion/conclusion: Results confirmed the quantitative relationship between syphilis stage and VDRL and TPPA titre identified previously. Additionally this study showed that IgM and IgG values, using Lab 21 IgM EIA and Abbott Architect Total Antibody Test assays, are also linked to stage of syphilis. Unsurprisingly, IgG titres were highest in secondary and lowest in primary syphilis. IgM values were lowest in early latent and highest in secondary syphilis.